AAGBI: Consent for anaesthesia 2017: Association of Anaesthetists of Great Britain and Ireland. (January 2017) - Yentis, S. M.; Hartle, A. J.; Barker, I. R.; Barker, P.; Bogod, D. G.; Clutton‐Brock, T. H.; Ruck Keene, A.; Leifer, S.; Naughton, A.; Plunkett, E.
Summary: Previous guidelines on consent for anaesthesia were issued by the Association of Anaesthetists of Great Britain and Ireland in 1999 and revised in 2006. The following guidelines have been produced in response to the changing ethical and legal background against which anaesthetists, and also intensivists and pain specialists, currently work, while retaining the key principles of respect for patients' autonomy and the need to provide adequate information. The main points of difference between the relevant legal frameworks in England and Wales and Scotland, Northern Ireland and the Republic of Ireland are also highlighted.